2019
DOI: 10.1080/03949370.2019.1620341
|View full text |Cite
|
Sign up to set email alerts
|

Differences in exploitation and interference ability between two dominant ants: the invasive Argentine ant (Linepithema humile) andTapinoma magnum

Abstract: Recruitment on bait GLMM results. (A) Comparisons between species in the foraging assay. (B)Comparisons between species in the resource competition assay. (C) Comparisons between assays within T. magnum. (D) Comparisons between assays within L. humile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…For instance, T. magnum Mayr has shown considerable potential as an invasive species in Northern Europe, where it thrives in many urban areas and is considered a pest [ 42 ]. A recent study showed that T. magnum was systematically excluded by L. humile from resources and underwent a visible reduction in activity [ 43 ]. The foraging activity of L. humile was nevertheless reduced in the presence of T. magnum due to an increased worker commitment, both in the arena fights and directly in the colony of the competitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, T. magnum Mayr has shown considerable potential as an invasive species in Northern Europe, where it thrives in many urban areas and is considered a pest [ 42 ]. A recent study showed that T. magnum was systematically excluded by L. humile from resources and underwent a visible reduction in activity [ 43 ]. The foraging activity of L. humile was nevertheless reduced in the presence of T. magnum due to an increased worker commitment, both in the arena fights and directly in the colony of the competitor.…”
Section: Discussionmentioning
confidence: 99%
“…niger was not excluded from the arena by L. humile , and its presence also resulted in a reduced foraging activity of L. humile due to an increased worker commitment in the arena fights. Moreover, Leonetti et al [ 43 ] suggested that the nest of the opponent could have been perceived as a new potential threat or resource and, therefore, a more valid target for recruitment than the trophic resource. However, this result could differ for other food contents, such as carbohydrate food that could be more attractive than protein sources [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…2017; Leonetti et al . 2019; Masoni et al . 2020), and its impact on biodiversity has been documented over a lengthy period (Holway et al .…”
Section: Introductionmentioning
confidence: 99%
“…2010; but see Neumann & Pinter‐Wollman 2022); other species, such as T. sessile and T. magnum , are instead outcompeted by L. humile when the whole colonies are involved (Buczkowski & Bennett 2008; Leonetti et al . 2019). Finally, L. neglectus showed a superior fighting ability in laboratory group fighting tests versus T. nigerrimum (Frizzi et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation